2020
DOI: 10.1103/physrevd.102.034511
|View full text |Cite
|
Sign up to set email alerts
|

Holography on tessellations of hyperbolic space

Abstract: We compute boundary correlation functions for scalar fields on tessellations of two-and threedimensional hyperbolic geometries. We present evidence that the continuum relation between the scalar bulk mass and the scaling dimension associated with boundary-to-boundary correlation functions survives the truncation of approximating the continuum hyperbolic space with a lattice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…Given these developments, one also anticipates implementations of hyperbolic lattices using other metamaterial platforms such as photonic crystals ( 8 , 9 ). The above concrete realizations of hyperbolic lattices in the laboratory open up vistas for the exploration of quantum mechanics in (negatively) curved space, with possibly far-reaching implications for fundamental physics in the areas of string theory ( 10 12 ), quantum gravity ( 13 – 15 ), and quantum information ( 16 21 ). In the long-wavelength limit, the Hamiltonian of a quantum particle on a hyperbolic lattice reduces to the well-known Laplace–Beltrami operator on the Poincaré disk ( 22 , 23 ), whose spectrum is well understood.…”
mentioning
confidence: 99%
“…Given these developments, one also anticipates implementations of hyperbolic lattices using other metamaterial platforms such as photonic crystals ( 8 , 9 ). The above concrete realizations of hyperbolic lattices in the laboratory open up vistas for the exploration of quantum mechanics in (negatively) curved space, with possibly far-reaching implications for fundamental physics in the areas of string theory ( 10 12 ), quantum gravity ( 13 – 15 ), and quantum information ( 16 21 ). In the long-wavelength limit, the Hamiltonian of a quantum particle on a hyperbolic lattice reduces to the well-known Laplace–Beltrami operator on the Poincaré disk ( 22 , 23 ), whose spectrum is well understood.…”
mentioning
confidence: 99%
“…Just as in the original Poincaré disk model, one can tessellate a timeslice of AdS spacetime; the resulting fractal pattern in the bulk of AdS breaks the continuous symmetries of the global conformal group 23 , 34 – 36 on the boundary. In 45 , it was shown that the holographic dictionary survives the truncation associated with approximating a continuous Poincaré disk model of AdS with a regular tessellation; moreover, as described in 26 , a tensor-network realization that imitates a tessellated Poincaré disk can be described using tensors at every vertex of the bulk. Conversely, edge tensors can be added to a tensor-network manifold that mimics the tessellated Poincaré disk, as in hyMERA.…”
Section: Quasiperiodic Boundaries and Variational Optimizationmentioning
confidence: 99%
“…1 Details of the lattice construction can be 1 Regular two-dimensional hyperbolic geometry can be represented by Schläfli symbol, {p, q} where p represents the p-sided polygon used as a building block to create the lattice and q represents the coordination number of each vertex found in Ref. [4]. The use of the triangle symmetry group for the lattice construction was also emphasized by Brower et al in Ref.…”
Section: The Model and Bulk Phase Structurementioning
confidence: 99%
“…For example: in previous work [4], we studied a model of a massive free scalar field propagating on tessellations of two and three-dimensional hyperbolic space. Despite strong lattice artifacts associated with finite lattice spacing and finite volume, the boundary lattice theory displays the usual features of conformality, exhibiting power-law fall-off of boundary-to-boundary correlators with boundary distance, where the inferred scaling dimensions match precisely with continuum analysis.…”
Section: Introductionmentioning
confidence: 99%

Holography for Ising spins on the hyperbolic plane

Asaduzzaman,
Catterall,
Hubisz
et al. 2021
Preprint
Self Cite